How to use Excel in analytical chemistry and in general scientific data analysis - De Levie, Robert (Cambridge University Press, 2001)
Because of their intuitive layout, extensive mathematical capabilities, and convenient graphics, spreadsheets provide an easy, straightforward route to scientific computing. This textbook for undergraduate and entry-level graduate chemistry and chemical engineering students uses Excel, the most powerful available spreadsheet package, to explore and solve problems in chemical analysis.